Characteristics of early Atlantic cod (Gadus morhua L.) catches based on otoliths recovered from archaeological excavations at medieval to early modern sites in northern Norway. (17th November 2022) - Pedersen, Torstein; Amundsen, Colin; Wickler, Stephen
Abstract: We compared stock origin, size- and age-distributions, and length growth rates derived from Atlantic cod otoliths from archaeological excavations at two sites in northern Norway: Vágar in Lofoten (68°12′N, ad 1156–1285) and the Værbukta site (70°57′N, ad 1450–1680). For comparison, modern otoliths were sampled during 1993–2001 from areas situated close to Vágar and Værbukta. Length-at-age from pre-20th century samples was back-calculated from otolith growth increments. The pre-20th century cod from Vágar was dominated by northeast Arctic cod (NEAC) of age 9–16 years and were much older and larger than the pre-20th century cod from Værbukta, which were dominated by coastal cod of age 2–6 years. Cod from Vágar had smaller increments and a shorter back-calculated length-at-age than modern cod from Lofoten. In contrast, the predominantly coastal cod from Værbukta had similar increments width and length-at-age as in modern samples. Age-distributions and mortality rates of the pre-20th century Vágar cod and NEAC from Lofoten in the 1930s were similar, indicating that both age at maturity and longevity were similar for these time periods. This contrasts with truncated and young age-distributions of spawning NEAC in the 1980s and 1990s following the strong increase in fishing and total mortality rate in the period 1955–2000.